The Rhetoric Topic of Borrowing in Advertising - Gabrėnaitė, Eglė (Respectus Philologicus, 2015)
The emotional appeal dominates in the persuasive discourse; usually, it is the rhetorical argumentation, the efficiency of which is closely related to the addressee value priorities. In order to achieve the advertising targets not only the newly discovered, but also the time-tested techniques of persuasion as well as the classic eristic argumentation models are employed.The research object of this article is the expression of borrowing topic in the advertising discourse. The aim of this research is to identify and describe the rhetoric topics, i.e., the mainrepeatable structural and conceptual models that act as arguments in the advertisements created by the companies providing quick loans. The analysis of rhetoric discourse allows to identify and describe the universal categories of argumentation, i.e., the rhetorical topics and their semantic and (or) structural modification in the persuasive discourses. The research reveals that the advertising of quick loans is based on the identical rhetorical topic expressed by the repeatable eristic arguments.Three following eristic arguments are identified and discussed: appealing to the masses (argumentum ad populum), appealing to time (argumentum ad tempus), appealing to safety (argumentum ad securitatem). It has been asserted that the advertising denies inconvenient and unsafe loan tradition. It patronizes unrestrained culture of lending where the loan is associated with the attractive images that eliminate the threat of social separation.
Keywords: rhetoric of advertising; rhetorical topic; eristic argument